Os contos da Geração 90 e da Geração McOndo : uma leitura latino-americana - Soares Filho, Daniel (2008)
By analyzing four short story anthologies two in the Portuguese language and two in the Spanish language , the present thesis on comparative literature proposes a study on the literary production in Latin America under the characteristics of Postmodernity described by Fredric Jameson. Taking into account the discussions about the literary concepts concerning the Hispanic-American and the Brazilian realities, the present work defines the use of terms related to Latin-American and points out the relations of the subcontinent with the contemporaneity. Such event formulates a justificative that allows understanding a generative proposal at the end of the twentieth century, presenting also the reasons that make possible recognize this group of short story writers as belonging to the same historical period, if we take into consideration the converging themes and the form that comprises their literary production. Therefore, this is the "90 Latin-American Generation".